Noncontact Knee Ligament Injury Prevention Screening in Netball: A Clinical Commentary with Clinical Practice Suggestions for Community-Level Players - Nicholas C Clark (International Journal of Sports Physical Therapy)
Netball is a predominantly female team court-sport which is played worldwide. Netball is becoming more popular in the United States following its countrywide introduction to schools and community centers. A unique characteristic of netball is the footwork rule which restricts players to a one-step landing after catching the ball. Most netball landings are single-leg landings resulting in high vertical ground reaction forces and high skeletal tissue forces. Thus, high-risk landing events that have the biomechanical potential for injury occur frequently. Noncontact knee ligament injuries are common following a knee abduction collapse when landing. Because the consequences of noncontact knee ligament injury are profound, strategies are needed to mitigate the burden of such injury for players, teams, and society.